An integrated conceptual framework for long‐term social–ecological research. Issue 6 (30th November 2010) - Collins, Scott L; Carpenter, Stephen R; Swinton, Scott M; Orenstein, Daniel E; Childers, Daniel L; Gragson, Ted L; Grimm, Nancy B; Grove, J Morgan; Harlan, Sharon L; Kaye, Jason P; Knapp, Alan K; Kofinas, Gary P; et al.
Abstract : The global reach of human activities affects all natural ecosystems, so that the environment is best viewed as a social–ecological system. Consequently, a more integrative approach to environmental science, one that bridges the biophysical and social domains, is sorely needed. Although models and frameworks for social–ecological systems exist, few are explicitly designed to guide a long‐term interdisciplinary research program. Here, we present an iterative framework, "Press–Pulse Dynamics" (PPD), that integrates the biophysical and social sciences through an understanding of how human behaviors affect "press" and "pulse" dynamics and ecosystem processes. Such dynamics and processes, in turn, influence ecosystem services –thereby altering human behaviors and initiating feedbacks that impact the original dynamics and processes. We believe that research guided by the PPD framework will lead to a more thorough understanding of social–ecological systems and generate the knowledge needed to address pervasive environmental problems.